IMPACT OF THE GOVERNMENT’S SOCIAL POLICY ON SPORTS DEVELOPMENT IN RUSSIA - Mikhail S. Nosov (Статистика и экономика, 2016)
This article focuses on interrelation between the government’s social policy and the level of sports development. This paper presents the comparative analysis of the average salary data in the countries worldwide and in Russia (by regions) and reports the level of teenage incidence.The article draws attention to the main reasons of low level of sports business in Russia and proposes important directions of social policy in the field of physical culture and sport.